Water-based paint for energy storage equipment and preparation method of water-based paint
By using fluorocarbon modified polyurethane dispersion and zirconium phosphate-polyaniline core-shell flame retardant in energy storage equipment coatings, the shortcomings of existing coatings in environmental protection and performance are solved, and the comprehensive performance of high weather resistance, flame retardancy, corrosion resistance, hardness and wear resistance are achieved, and the protection effect of energy storage equipment is comprehensively improved.
Patent Information
- Application Number
- CN202510399504.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-06-17
- Estimated Expiration
- 2045-04-01
AI Technical Summary
The existing energy storage equipment coatings have shortcomings in terms of environmental protection and performance, solvent-based coatings have poor environmental protection, water-based coatings have insufficient coating hardness and wear resistance, and poor protection effect in high humidity and strong corrosion environments.
A water-based coating with high weather resistance, flame retardant, ZnNiAl-LDH two-dimensional layered trimetal hydroxide, nanosilica, nanoceria, nanoceria and other components were prepared with aqueous silicone modified acrylic resin and aqueous epoxy ester resin.
This water-based coating has good weather resistance and flame retardant in terms of protection performance, excellent corrosion resistance, high hardness and wear resistance, ensuring that the coating is firmly combined with the equipment surface, comprehensively protecting energy storage equipment, and improving its reliability, safety and service life.
Smart Images

Figure BDA0005339426510000141
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of coatings, and particularly relates to an aqueous coating for energy storage devices and a preparation method thereof. Background Art
[0002] In the process of actively promoting energy transformation and sustainable development, energy storage technology has become a key support in the energy field. As a carrier for storing and releasing electrical energy, energy storage devices have become increasingly important and play an irreplaceable role in multiple key fields. Common energy storage devices include battery energy storage systems such as lead-acid batteries, lithium-ion batteries, and sodium-sulfur batteries, as well as physical energy storage methods such as pumped-storage energy storage, compressed-air energy storage, and flywheel energy storage.
[0003] In a complex operating environment, energy storage devices face various types of erosion; outdoor energy storage devices are exposed to ultraviolet radiation all year round, which can cause the outer shell to age; in a humid environment, it is easy to cause corrosion of metal components, reducing the performance and lifespan of the device. Therefore, energy storage devices usually need to be painted for protection. Painting can form a barrier to block ultraviolet rays, water vapor, chemical substances, etc., and protect the device substrate. On the other hand, painting can improve the safety of the device. Some special coatings have flame-retardant and anti-static properties, which can reduce the risks of fire and static electricity hazards and ensure the safe and stable operation of energy storage devices.
[0004] Currently, the coatings applied to energy storage devices are mainly solvent-based coatings and aqueous coatings. Solvent-based coatings have good film-forming properties and excellent mechanical properties, but they contain a large amount of volatile organic compounds (VOCs), which will pollute the environment and endanger human health during production, construction, and use. Aqueous coatings use water as a diluent and have the advantages of environmental protection, low toxicity, and safety, which conform to the current environmental protection concept and have developed rapidly in recent years.
[0005] The coatings for energy storage devices need to possess multiple properties. In terms of protective properties, they should have good weather resistance, be able to resist ultraviolet rays and high-low temperature cycles for a long time, prevent the coating from powdering and fading; excellent corrosion resistance, resist the erosion of chemical substances such as acids, alkalis, and salts; and excellent waterproofness, prevent water penetration. In terms of mechanical properties, high hardness and wear resistance are indispensable, which can withstand daily friction and collision; good flexibility, so that the coating does not crack or peel off when the device vibrates or deforms. In addition, good adhesion is also required to ensure that the coating is firmly bonded to the device surface; in some scenarios, the coating should also possess special functions such as fire protection and anti-static.
[0006] Although there are various coatings on the existing market, there are still many problems with coatings for energy storage devices, mainly including the following points: (1) Although solvent-based coatings have good performance, they have poor environmental friendliness and are restricted in use with the tightening of environmental protection regulations. (2) Although water-based coatings are environmentally friendly, the hardness and abrasion resistance of the coating films are insufficient, and they are easily scratched and worn during use; there are gaps in performance such as salt spray corrosion resistance, weather resistance, and flame retardancy compared with solvent-based coatings, and the protection effect is poor in high humidity and strong corrosion environments.
[0007] Therefore, it is necessary to continuously develop high-performance, environmentally friendly and excellent comprehensive performance coatings for energy storage devices to promote the development of the energy storage device industry and improve the reliability, safety and service life of the devices. Summary of the Invention
[0008] Aiming at the problems of poor environmental friendliness of existing solvent-based coatings and the unsatisfactory above-mentioned various performance indexes of water-based coatings. The present invention provides a water-based coating for energy storage devices and a preparation method thereof. A fluorocarbon-modified polyurethane dispersion and a zirconium phosphate-polyaniline core-shell flame retardant are prepared by a special method, and then used in combination with other components such as ZnNiAl-LDH two-dimensional layered trimetallic hydroxide, C18-36 acid glycol ester, water-based organosilicon-modified acrylic resin, water-based epoxy ester resin, nano-silica, nano-cerium oxide, etc., so that the coating has good weather resistance and flame retardancy, excellent corrosion resistance, high hardness and abrasion resistance, and also has good adhesion, ensuring that the coating is firmly combined with the surface of the device, comprehensively protecting the energy storage device, and improving its reliability, safety and service life. The specific technical solutions are as follows:
[0009] A water-based coating for energy storage devices, comprising the following raw materials in parts by mass: 10 parts to 15 parts of fluorocarbon-modified polyurethane dispersion, 15 parts to 20 parts of water-based epoxy ester resin, 30 parts to 35 parts of water-based organosilicon-modified acrylic resin, 0.5 part to 1 part of ZnNiAl-LDH two-dimensional layered trimetallic hydroxide, 6 parts to 8 parts of zirconium phosphate-polyaniline core-shell flame retardant, 8 parts to 10 parts of nano-silica, 4 parts to 6 parts of water-based polycarbodiimide, 1 part to 2 parts of nano-cerium oxide, 0.5 part to 0.8 part of polyether-modified organosilicon defoamer, 3 parts to 5 parts of C18-36 acid glycol ester, 0.3 part to 0.8 part of leveling agent, 3 parts to 6 parts of pigment, 5 parts to 8 parts of 1-ethoxy-2-propanol, and the balance is water, and the solid content is 45wt% to 50wt%.
[0010] In the above-mentioned waterborne coating, the preparation method of the fluorocarbon-modified polyurethane dispersion comprises the following steps: by mass parts, 40 to 50 parts of isophorone diisocyanate, 20 to 25 parts of hexafluorobutane diol, 30 to 35 parts of polypropylene oxide ether diol, and 3 to 5 parts of C20-22 alcohol phosphate. Under nitrogen protection, stir and mix evenly at 75°C to 85°C to obtain a mixed liquid A. Add dibutyltin dilaurate and stir to react to obtain a reaction liquid B; cool down to 55°C to 65°C, add 5 to 8 parts of dimethylolpropionic acid and 100 to 120 parts of acetone, continue to stir and react. After the reaction is completed, add triethylamine to neutralize the pH value to 7 to 8, and then add 120 to 150 parts of deionized water under high-speed shearing to form a stable dispersion with a particle size below 200 nm. Remove acetone and part of the deionized water by vacuum distillation to obtain a fluorocarbon-modified polyurethane dispersion with a solid content of 40 wt% to 50 wt%.
[0011] In the preparation method of the above-mentioned fluorocarbon-modified polyurethane dispersion, the addition amount of the dibutyltin dilaurate is 0.05% to 0.08% of the mass of the mixed liquid A.
[0012] In the preparation method of the above-mentioned fluorocarbon-modified polyurethane dispersion, the rotation speed of the stirring reaction is 300 r / min to 500 r / min; the time of the stirring reaction is 3 h to 4 h; the rotation speed of the high-speed shearing is 3000 rpm to 5000 rpm.
[0013] In the above-mentioned waterborne coating, the preparation method of the zirconium phosphate-polyaniline core-shell flame retardant comprises the following steps: Add zirconium phosphate to ethanol, disperse it evenly by ultrasonic wave, add 6 wt% to 8 wt% of γ-aminopropyltriethoxysilane based on the mass of zirconium phosphate, stir and react for 2 h to 3 h, centrifuge, take the precipitate and wash it with absolute ethanol, and dry it to obtain the treated zirconium phosphate; Add the treated zirconium phosphate to the hydrochloric acid solution, disperse it by ultrasonic wave, add aniline according to the mass ratio of aniline:treated zirconium phosphate = (2 to 3):1 at 2°C to 6°C, mix evenly, and then add an aqueous solution of ammonium persulfate, stir and polymerize for 6 h to 8 h, centrifuge, take the precipitate and wash it alternately with deionized water and ethanol, and dry it to obtain the zirconium phosphate-polyaniline core-shell flame retardant.
[0014] In the preparation method of the above-mentioned zirconium phosphate-polyaniline core-shell flame retardant, the particle size of the zirconium phosphate is nanoscale; the dosage of the ethanol is 10 to 12 times the mass of the zirconium phosphate; the dosage of the hydrochloric acid solution is 10 to 12 times the mass of the treated zirconium phosphate; the hydrochloric acid solution is a hydrochloric acid aqueous solution with a concentration of 1 mol / L to 1.5 mol / L, and the hydrochloric acid solution contains 5 g / 100 mL to 8 g / 100 mL of camphorsulfonic acid; the concentration of the ammonium persulfate aqueous solution is 50 g / 100 mL to 60 g / 100 mL.
[0015] In the preparation method of the above-mentioned zirconium phosphate-polyaniline core-shell flame retardant, the frequency of the ultrasonic dispersion is 40 kHz to 60 kHz, the power is 150 W to 250 W, and the time is 30 min to 60 min; the rotation speed of the stirring is 300 r / min to 500 r / min; the centrifugation is carried out at 5000 r / min to 8000 r / min for 10 min to 20 min.
[0016] In the preparation method of the above-mentioned zirconium phosphate-polyaniline core-shell flame retardant, the number of times of washing with absolute ethanol is 2 to 3 times; the deionized water and ethanol are alternately washed 2 to 3 times each; the drying is carried out in vacuum at 60 °C to 80 °C for 4 h to 8 h.
[0017] The preparation method of the above-mentioned waterborne coating for energy storage devices includes the following steps:
[0018] S1: By mass, ZnNiAl-LDH two-dimensional layered trimetallic hydroxide, zirconium phosphate-polyaniline core-shell flame retardant, nano-silica and nano-ceria are mixed evenly by air flow to obtain a mixed powder;
[0019] S2: By mass, waterborne epoxy ester resin, waterborne organosilicon-modified acrylic resin and 1-ethoxy-2-propanol are stirred and mixed, then the mixed powder and pigments are added, stirred and mixed, and then polyether-modified organosilicon defoamer, leveling agent, C18-36 acid glycol ester are added in turn, stirred and mixed, and finally waterborne polycarbodiimide and fluorocarbon-modified polyurethane dispersion are added, stirred and mixed to obtain a mixed material;
[0020] S3: The mixed material is transferred to a high-speed disperser for high-speed dispersion, then ground, and water is added to adjust the solid content of the system to 45 wt% to 50 wt%, and stirred and mixed evenly to obtain a waterborne coating.
[0021] In the preparation method of the above-mentioned waterborne coating, the rotation speed of the stirring and mixing is 300 r / min to 500 r / min, and the time of the stirring and mixing is 15 min to 20 min; the high-speed dispersion is carried out at 3000 rpm to 5000 rpm for 30 min to 60 min; the parameters of the grinding are: the grinding medium is zirconia with a particle size of 0.1 mm to 0.3 mm, the grinding rotation speed is 1500 rpm to 2500 rpm; the feeding speed is 2 L / min to 3 L / min.
[0022] A waterborne coating for energy storage devices and its preparation method provided by the present invention have the following beneficial effects:
[0023] 1. In the preparation method of fluorocarbon modified polyurethane dispersion, isophorone diisocyanate, as a multifunctional isocyanate, has high reactivity and can undergo step-by-step polymerization reaction with hexafluorobutanediol and polyoxypropylene ether diol. Under the action of dibutyltin dilaurate, a highly efficient catalyst, the reaction rate is significantly improved to generate a prepolymer containing isocyanate groups. The introduction of dimethylol propionic acid is crucial. It successfully introduces carboxyl groups into the prepolymer through chemical reactions. The carboxyl groups are subsequently neutralized with triethylamine, so that the entire system can form a stable dispersion in water. Among them, C20-22 alcohol phosphate has a special molecular structure, and its addition can adjust the performance of fluorocarbon modified polyurethane dispersion. The phosphate group can enhance the interaction between molecules and make the arrangement between polyurethane molecular chains more compact, thereby improving the stability and mechanical properties of the dispersion. At the same time, the long-chain C20-22 alcohol part can improve the flexibility and water resistance of the dispersion, so that the final fluorocarbon modified polyurethane dispersion can better adapt to different use environments when applied to water-based coatings. C20-22 alcohol phosphate can play a certain catalytic and promoting role in the reaction, which helps the reaction between raw materials such as isophorone diisocyanate, hexafluorobutanediol, and polyoxypropylene ether diol to proceed more smoothly, enables the reaction system to be mixed more evenly, and improves the reaction efficiency and product quality.
[0024] The fluorocarbon segment, with its unique chemical structure, gives the coating excellent weather resistance, and can effectively resist long-term exposure to ultraviolet rays without degradation and discoloration; its low surface energy characteristics make the coating have good water resistance, and water droplets are difficult to adhere to and penetrate the coating surface; the polyurethane structure gives the coating good flexibility, which can adapt to the slight deformation of energy storage equipment under different environmental conditions, while providing high mechanical strength and enhancing the coating's wear and impact resistance. When the dispersion forms a film in conjunction with other resins, it can significantly enhance the toughness of the entire coating and improve the adhesion of the coating to the substrate of the energy storage device, ensuring that when the vibration or temperature of the energy storage device changes, the coating can still firmly adhere to the surface of the device without cracking or falling off.
[0025] II. In the preparation of zirconium phosphate-polyaniline core-shell flame retardant, γ-aminopropyltriethoxysilane plays a crucial role in the surface modification of zirconium phosphate. It can introduce organic functional groups on the surface of zirconium phosphate, greatly improving the compatibility between zirconium phosphate and organic substances, and providing a good foundation for the subsequent polymerization of polyaniline on its surface. In an acidic hydrochloric acid aqueous solution environment, ammonium persulfate, as an initiator, can generate free radicals to initiate the polymerization reaction between aniline molecules. Since zirconium phosphate has been surface-treated, aniline preferentially polymerizes on its surface, gradually forming a polyaniline shell layer, thus constructing a zirconium phosphate-polyaniline core-shell structure. Zirconium phosphate itself has high heat resistance and flame retardancy, and can effectively inhibit the spread and propagation of flames in a high-temperature environment; polyaniline not only has good electrical conductivity, which can effectively reduce the risk of static electricity accumulation. For energy storage devices that are prone to generating static electricity, it greatly ensures their safe operation. It also has certain antioxidant properties, which can protect zirconium phosphate from oxidation to a certain extent and extend its service life. The core-shell structure formed by the combination of the two forms a synergistic charring mechanism of expansion, enabling the flame retardant to improve the flame retardant performance of the coating while also enhancing the electrical and antioxidant properties of the coating.
[0026] III. In waterborne coatings, ZnNiAl-LDH two-dimensional layered trimetallic hydroxide has a special layered structure and ion exchange properties, and can adsorb harmful substances that may exist in the coating system, effectively improving the corrosion resistance of the coating and providing protection for energy storage devices in a complex chemical environment. Due to its nano-scale size effect, nano-silica can increase the hardness of the coating, making it more resistant to friction and scratching; enhance the abrasion resistance of the coating and extend the service life of the coating; at the same time, it can also improve the weather resistance of the coating and enhance the coating's ability to resist ultraviolet rays and temperature changes; and during the construction process of the coating, it can adjust the rheology of the coating, making the coating have good leveling properties and ensuring a smooth and flat coating surface. Nano-ceria has excellent antioxidant properties and can effectively inhibit the oxidative degradation reaction of the coating during use; at the same time, it has a strong absorption capacity for ultraviolet rays, which can protect the organic components in the coating from being damaged by ultraviolet rays, greatly improving the weather resistance and anti-aging performance of the coating.
[0027] IV. In this coating system, polyaniline can isolate zirconium phosphate, thereby protecting the ZnNiAl-LDH two-dimensional layered trimetallic hydroxide from the acidic influence of zirconium phosphate. Zirconium phosphate itself is weakly acidic, but during the preparation of zirconium phosphate-polyaniline core-shell flame retardant, after a series of treatments, the surface of zirconium phosphate is coated with polyaniline to form a core-shell structure. Polyaniline can isolate zirconium phosphate, thereby protecting the ZnNiAl-LDH two-dimensional layered trimetallic hydroxide from the acidic influence of zirconium phosphate, preventing structural damage and dissolution; in addition, other basic and neutral components in the coating will also play a certain buffering and regulating role in the acidity and alkalinity of the system, jointly maintaining the stability of the coating system.
[0028] V. In waterborne coatings, waterborne epoxy ester resin can react chemically with the active groups on the surface of the substrate of energy storage devices due to the epoxy groups and ester groups in its molecular structure, thus providing good adhesion. At the same time, it also has good chemical corrosion resistance and can resist the erosion of chemical substances such as acids and alkalis on the coating. Waterborne silicone-modified acrylic resin combines the advantages of silicone and acrylic resin. The silicone part endows the coating with good weather resistance, heat resistance and water resistance, enabling it to be used outdoors for a long time without performance degradation; the acrylic resin part provides good film-forming property and gloss, making the coating have an aesthetic decorative effect. 1-Ethoxy-2-propanol, as a solvent, can adjust the viscosity of the coating, making it have good fluidity and operability during construction; at the same time, it can also control the drying speed of the coating to ensure that the coating forms a uniform and dense structure during drying. C18-36 acid glycol ester can improve the film-forming performance of the coating and increase the density of the coating. In addition, C18-36 acid glycol ester can insert between the polymer chains of the coating to improve the flexibility of the coating, so that it can maintain good physical properties at low temperatures and is not prone to cracking. Waterborne polycarbodiimide, as a crosslinking agent, can react with other components in the coating, such as waterborne epoxy ester resin, fluorocarbon-modified polyurethane dispersion, etc., to form a three-dimensional network structure between molecules, greatly improving the hardness, wear resistance and water resistance of the coating. Fluorocarbon-modified polyurethane dispersion further enhances the weather resistance, flexibility and mechanical properties of the coating, and synergistically with other components, enables the coating to better adapt to the working environment of energy storage devices. Through step-by-step stirring and mixing, the components interact and blend with each other, initially forming a system with complementary properties.
[0029] In summary, the components act synergistically in the whole system, enabling the coating to have good weather resistance in terms of protective performance, being able to resist the influence of ultraviolet rays and high and low temperature cycles for a long time, preventing the coating from powdering and fading; having excellent corrosion resistance and effectively resisting the erosion of chemical substances such as acids, alkalis and salts; in terms of mechanical properties, having high hardness and wear resistance and being able to withstand daily friction and collision; also having good adhesion to ensure that the coating is firmly bonded to the surface of the device. In addition, the coating also has special functions such as flame retardancy, comprehensively protecting the energy storage device and improving its reliability, safety and service life. Specific Embodiments
[0030] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to these embodiments.
[0031] Example 1
[0032] An aqueous coating for energy storage devices, comprising raw materials in the following parts by mass: 13 parts of fluorocarbon-modified polyurethane dispersion, 17 parts of waterborne epoxy ester resin, 32 parts of waterborne silicone-modified acrylic resin, 0.6 part of ZnNiAl-LDH two-dimensional layered trimetallic hydroxide, 7 parts of zirconium phosphate-polyaniline core-shell flame retardant, 9 parts of nano-silica, 5 parts of waterborne polycarbodiimide, 1.5 parts of nano-cerium oxide, 0.6 part of polyether-modified silicone defoamer, 4 parts of C18-36 acid glycol ester, 0.5 part of leveling agent, 4 parts of pigment, 6 parts of 1-ethoxy-2-propanol, and the balance is water, with a solid content of 48 wt%.
[0033] Among them, the preparation method of the fluorocarbon-modified polyurethane dispersion includes the following steps: According to the parts by mass, 45 parts of isophorone diisocyanate, 23 parts of hexafluorobutylene glycol, 32 parts of polypropylene oxide ether diol, and 4 parts of C20-22 alcohol phosphate ester are stirred and mixed evenly at 80 °C under nitrogen protection to obtain a mixed solution A. 0.06% of dibutyltin dilaurate based on the mass of the mixed solution A is added, and the reaction is stirred at 400 r / min for 3.5 h to obtain a reaction solution B; the temperature is lowered to 60 °C, 6 parts of dimethylolpropionic acid and 110 parts of acetone are added, and the reaction is continued to stir at 400 r / min for 3.5 h. After the reaction is completed, triethylamine is added to neutralize the pH value to 7.5, and then 130 parts of deionized water are added under high-speed shearing at 4000 rpm to form a stable dispersion with a particle size below 200 nm. Acetone and part of the deionized water are removed by vacuum distillation to obtain a fluorocarbon-modified polyurethane dispersion with a solid content of 45 wt%.
[0034] Among them, the preparation method of the zirconium phosphate-polyaniline core-shell flame retardant includes the following steps: Nano-sized zirconium phosphate is added to 11 times its mass of ethanol, ultrasonically dispersed at 200 W and 50 kHz for 50 min, 7 wt% of γ-aminopropyltriethoxysilane based on the mass of zirconium phosphate is added, and the reaction is stirred at 400 r / min for 2.5 h, centrifuged at 6000 r / min for 15 min, and the precipitate is washed twice with absolute ethanol and vacuum dried at 70 °C for 6 h to obtain treated zirconium phosphate; a 1.2 mol / L hydrochloric acid aqueous solution containing 6.5 g / 100 mL of camphorsulfonic acid is prepared; the treated zirconium phosphate is added to 11 times its mass of hydrochloric acid solution, ultrasonically dispersed at 200 W and 50 kHz for 50 min, and aniline is added at 4 °C according to the mass ratio of aniline:treated zirconium phosphate = 2.5:1, mixed evenly, and then an aqueous solution of ammonium persulfate with a concentration of 55 g / 100 mL is added, and the polymerization reaction is stirred at 400 r / min for 7 h, centrifuged at 6000 r / min for 15 min, and the precipitate is washed twice with deionized water and ethanol alternately and vacuum dried at 70 °C for 6 h to obtain the zirconium phosphate-polyaniline core-shell flame retardant.
[0035] The preparation method of the above-mentioned aqueous coating for energy storage devices includes the following steps:
[0036] S1: By mass parts, uniformly mix ZnNiAl-LDH two-dimensional layered trimetallic hydroxide, zirconium phosphate-polyaniline core-shell flame retardant, nano-silica and nano-ceria by air flow to obtain a mixed powder;
[0037] S2: By mass parts, stir and mix waterborne epoxy ester resin, waterborne organosilicon-modified acrylic resin and 1-ethoxy-2-propanol at 400 r / min for 18 min, then add the mixed powder and pigments, stir and mix at 400 r / min for 18 min, and then successively add polyether-modified organosilicon defoamer, leveling agent, C18-36 acid glycol ester, stir and mix at 400 r / min for 16 min, and finally add waterborne polycarbodiimide and fluorocarbon-modified polyurethane dispersion, stir and mix at 400 r / min for 16 min to obtain a mixed material;
[0038] S3: Transfer the mixed material to a high-speed disperser, disperse it at a high speed of 4000 rpm for 50 min, then grind it. The grinding medium is zirconia with a particle size of 0.2 mm, the grinding speed is 2000 rpm; the feeding speed is 2.5 L / min. After grinding, add water to adjust the solid content of the system to 48 wt%, and stir and mix evenly at 400 r / min to obtain a waterborne coating.
[0039] Example 2
[0040] A waterborne coating for energy storage devices, comprising the following raw materials by mass parts: 10 parts of fluorocarbon-modified polyurethane dispersion, 15 parts of waterborne epoxy ester resin, 30 parts of waterborne organosilicon-modified acrylic resin, 0.5 part of ZnNiAl-LDH two-dimensional layered trimetallic hydroxide, 6 parts of zirconium phosphate-polyaniline core-shell flame retardant, 8 parts of nano-silica, 4 parts of waterborne polycarbodiimide, 1 part of nano-ceria, 0.5 part of polyether-modified organosilicon defoamer, 3 parts of C18-36 acid glycol ester, 0.3 part of leveling agent, 3 parts of pigments, 5 parts of 1-ethoxy-2-propanol, and the balance is water, with a solid content of 45 wt%.
[0041] Among them, the preparation method of the fluorocarbon-modified polyurethane dispersion includes the following steps: By mass parts, 40 parts of isophorone diisocyanate, 20 parts of hexafluorobutylene glycol, 30 parts of polypropylene oxide ether diol, and 3 parts of C20-22 alcohol phosphate are stirred and mixed evenly at 75 °C under nitrogen protection to obtain a mixed liquid A. Then, 0.05% of dibutyltin dilaurate based on the mass of the mixed liquid A is added, and the mixture is stirred and reacted at 300 r / min for 3 h to obtain a reaction liquid B. The temperature is lowered to 55 °C, 5 parts of dimethylolpropionic acid and 100 parts of acetone are added, and the mixture is continuously stirred and reacted at 300 r / min for 3 h. After the reaction is completed, triethylamine is added to neutralize the pH value to 7, and then 120 parts of deionized water are added under high-speed shearing at 3000 rpm to form a stable dispersion with a particle size below 200 nm. Acetone and part of the deionized water are removed by vacuum distillation to obtain a fluorocarbon-modified polyurethane dispersion with a solid content of 40 wt%.
[0042] Among them, the preparation method of the zirconium phosphate-polyaniline core-shell flame retardant includes the following steps: Nanoscale zirconium phosphate is added to ethanol with a mass 10 times that of zirconium phosphate, and ultrasonic dispersion is carried out at 150 W and 40 kHz for 30 min. Then, 6 wt% of γ-aminopropyltriethoxysilane based on the mass of zirconium phosphate is added, and the mixture is stirred and reacted at 300 r / min for 2 h. After centrifugation at 5000 r / min for 10 min, the precipitate is taken and washed twice with absolute ethanol, and then vacuum dried at 60 °C for 4 h to obtain the treated zirconium phosphate. A 1 mol / L hydrochloric acid aqueous solution containing 5 g / 100 mL of camphorsulfonic acid is prepared. The treated zirconium phosphate is added to a hydrochloric acid solution with a mass 10 times that of zirconium phosphate, and ultrasonic dispersion is carried out at 150 W and 40 kHz for 30 min. According to the mass ratio of aniline:treated zirconium phosphate = 2:1, aniline is added at 2 °C and mixed evenly. Then, an aqueous ammonium persulfate solution with a concentration of 50 g / 100 mL is added, and the mixture is stirred and polymerized at 300 r / min for 6 h. After centrifugation at 5000 r / min for 10 min, the precipitate is taken and washed twice alternately with deionized water and ethanol, and then vacuum dried at 60 °C for 4 h to obtain the zirconium phosphate-polyaniline core-shell flame retardant.
[0043] The preparation method of the above-mentioned waterborne coating for energy storage devices includes the following steps:
[0044] S1: By mass parts, ZnNiAl-LDH two-dimensional layered trimetallic hydroxide, zirconium phosphate-polyaniline core-shell flame retardant, nano-silica, and nano-ceria are mixed evenly by air flow to obtain a mixed powder;
[0045] S2: By mass parts, stir and mix waterborne epoxy ester resin, waterborne organosilicon-modified acrylic resin and 1-ethoxy-2-propanol at 300 r / min for 15 min. Then add the mixed powder and pigment, and stir and mix at 300 r / min for 15 min. After that, add polyether-modified organosilicon defoamer, leveling agent, and C18-36 acid glycol ester in sequence, stir and mix at 300 r / min for 15 min. Finally, add waterborne polycarbodiimide and fluorocarbon-modified polyurethane dispersion, stir and mix at 300 r / min for 15 min to obtain a mixed material.
[0046] S3: Transfer the mixed material to a high-speed disperser, perform high-speed dispersion at 3000 rpm for 30 min, then carry out grinding. The grinding medium is zirconia with a particle size of 0.1 mm, and the grinding speed is 1500 rpm; the feeding speed is 2 L / min. After grinding, add water to adjust the solid content of the system to 45 wt%, and stir and mix evenly at 300 r / min to obtain a waterborne coating.
[0047] Example 3
[0048] A waterborne coating for energy storage devices, comprising raw materials in the following mass parts: 15 parts of fluorocarbon-modified polyurethane dispersion, 20 parts of waterborne epoxy ester resin, 35 parts of waterborne organosilicon-modified acrylic resin, 1 part of ZnNiAl-LDH two-dimensional layered trimetallic hydroxide, 8 parts of zirconium phosphate-polyaniline core-shell flame retardant, 10 parts of nano-silica, 6 parts of waterborne polycarbodiimide, 2 parts of nano-cerium oxide, 0.8 part of polyether-modified organosilicon defoamer, 5 parts of C18-36 acid glycol ester, 0.8 part of leveling agent, 6 parts of pigment, 8 parts of 1-ethoxy-2-propanol, with the balance being water and the solid content being 50 wt%.
[0049] Among them, the preparation method of the fluorocarbon-modified polyurethane dispersion includes the following steps: By mass parts, 50 parts of isophorone diisocyanate, 25 parts of hexafluorobutylene glycol, 35 parts of polypropylene oxide ether diol, and 5 parts of C20-22 alcohol phosphate ester. Under nitrogen protection, stir and mix evenly at 85 °C to obtain a mixed liquid A. Add dibutyltin dilaurate accounting for 0.08% of the mass of the mixed liquid A, and stir and react at 500 r / min for 4 h to obtain a reaction liquid B; cool down to 65 °C, add 8 parts of dimethylolpropionic acid and 120 parts of acetone, continue to stir and react at 500 r / min for 4 h. After the reaction ends, add triethylamine to neutralize the pH value to 8, and then add 150 parts of deionized water under high-speed shearing at 5000 rpm to form a stable dispersion with a particle size below 200 nm. Remove acetone and part of the deionized water by vacuum distillation to obtain a fluorocarbon-modified polyurethane dispersion with a solid content of 50 wt%.
[0050] Among them, the preparation method of the zirconium phosphate-polyaniline core-shell flame retardant includes the following steps: adding zirconium phosphate with a nanoscale particle size into ethanol with a mass 12 times that of zirconium phosphate, performing ultrasonic dispersion at 250 W and 60 kHz for 60 min, adding γ-aminopropyltriethoxysilane accounting for 8 wt% of the mass of zirconium phosphate, stirring and reacting at 500 r / min for 3 h, centrifuging at 8000 r / min for 20 min, taking the precipitate, washing it 3 times with absolute ethanol, and drying it in vacuum at 80 °C for 8 h to obtain the treated zirconium phosphate; preparing a 1.5 mol / L hydrochloric acid aqueous solution containing 8 g / 100 mL of camphorsulfonic acid; adding the treated zirconium phosphate into a hydrochloric acid solution with a mass 12 times that of zirconium phosphate, performing ultrasonic dispersion at 250 W and 60 kHz for 60 min, adding aniline at a mass ratio of aniline:treated zirconium phosphate = 3:1 at 6 °C, mixing evenly, then adding an aqueous ammonium persulfate solution with a concentration of 60 g / 100 mL, stirring and polymerizing at 500 r / min for 8 h, centrifuging at 8000 r / min for 20 min, taking the precipitate, washing it 3 times each with deionized water and ethanol alternately, and drying it in vacuum at 80 °C for 8 h to obtain the zirconium phosphate-polyaniline core-shell flame retardant.
[0051] The preparation method of the above-mentioned waterborne coating for energy storage devices includes the following steps:
[0052] S1: According to parts by mass, uniformly mixing ZnNiAl-LDH two-dimensional layered trimetallic hydroxide, zirconium phosphate-polyaniline core-shell flame retardant, nano-silica and nano-cerium oxide by air flow to obtain a mixed powder;
[0053] S2: According to parts by mass, stirring and mixing waterborne epoxy ester resin, waterborne organosilicon-modified acrylic resin and 1-ethoxy-2-propanol at 500 r / min for 20 min, then adding the mixed powder and pigment, stirring and mixing at 500 r / min for 20 min, then sequentially adding polyether-modified organosilicon defoamer, leveling agent, C18-36 acid glycol ester, stirring and mixing at 500 r / min for 20 min, and finally adding waterborne polycarbodiimide and fluorocarbon-modified polyurethane dispersion, stirring and mixing at 500 r / min for 20 min to obtain a mixed material;
[0054] S3: Transfer the mixed material to a high-speed disperser, perform high-speed dispersion at 5000 rpm for 60 min, then perform grinding. The grinding medium is zirconia with a particle size of 0.3 mm, the grinding speed is 2500 rpm; the feeding speed is 3 L / min. After grinding, add water to adjust the solid content of the system to 50 wt%, and stir and mix evenly at 500 r / min to obtain the waterborne coating.
[0055] In the above embodiments: The waterborne epoxy ester resin is from Foshan Wansha New Material Technology Co., Ltd., model WX-SH, with a solid content of 70 wt%, and a molecular weight of 10,000 - 12,000. The waterborne silicone-modified acrylic resin is from Qingdao Wanjiahuixin Surface Material Technology Co., Ltd., model S-611, with a solid content of 40 wt%, and a viscosity of 3500 - 4000 (S). ZnNiAl-LDH two-dimensional layered trimetallic hydroxide is from Jiangsu Xianfeng Nano Material Technology Co., Ltd., model XFL03. Nano-silica is from Nanjing Baokete New Material Co., Ltd., model PST-Q02. The waterborne polycarbodiimide is from Shanghai Youen Chemical Co., Ltd., a multifunctional polycarbodiimide, model UN-557. Nano-cerium oxide is from Hangzhou Jiupeng New Material Co., Ltd. The polyether-modified silicone defoamer is from Shanghai Huiyan New Material Co., Ltd., model HY-6803. C18-36 acid glycol ester is from Beijing Huamei Huli Biochemical Co., Ltd. The leveling agent is from Guangdong Zhongtai Lianhua New Material Co., Ltd., model AG-295, with a composition of polyether-modified polysiloxane polymer. Polypropylene glycol ether diol is from Shandong Baihong New Material Co., Ltd., model DL4000D. C20-22 alcohol phosphate is from Hubei Xinyuhong Biomedical Technology Co., Ltd. Zirconium phosphate is from Mianzhu Yaolong Chemical Co., Ltd., nano-scale. γ-aminopropyltriethoxysilane is from Shandong Moore Chemical Co., Ltd., model 101. Camphorsulfonic acid is from Shanghai Aoji Chemical Co., Ltd., racemic camphorsulfonic acid.
[0056] Comparative Example 1
[0057] In the coating, the fluorocarbon-modified polyurethane dispersion is replaced with a waterborne polyurethane emulsion with a solid content of 45 wt% (the polyurethane is from Anhui Femtosecond Chemical Co., Ltd., model FS-108C); other parameters and methods are the same as in Example 1.
[0058] Comparative Example 2
[0059] In the preparation method of the fluorocarbon-modified polyurethane dispersion, C20-22 alcohol phosphate is not added; other parameters and methods are the same as in Example 1.
[0060] Comparative Example 3
[0061] In the preparation method of the fluorocarbon-modified polyurethane dispersion, 15 parts (excessive) of C20-22 alcohol phosphate are added; other parameters and methods are the same as in Example 1.
[0062] Comparative Example 4
[0063] In the coating, the zirconium phosphate-polyaniline core-shell flame retardant is replaced with zirconium phosphate; other parameters and methods are the same as in Example 1.
[0064] Comparative Example 5
[0065] In the preparation method of the zirconium phosphate-polyaniline core-shell flame retardant, zirconium phosphate is not pretreated on the surface with γ-aminopropyltriethoxysilane; other parameters and methods are the same as those in Example 1.
[0066] Comparative Example 6
[0067] In the coating, ZnNiAl-LDH two-dimensional layered trimetallic hydroxide is not added; other parameters and methods are the same as those in Example 1.
[0068] Comparative Example 7
[0069] In the coating, C18-36 acid glycol ester is not added; other parameters and methods are the same as those in Example 1.
[0070] Comparative Example 8
[0071] In the coating, the zirconium phosphate-polyaniline core-shell flame retardant is replaced with zirconium phosphate; ZnNiAl-LDH two-dimensional layered trimetallic hydroxide is not added; other parameters and methods are the same as those in Example 1.
[0072] For the convenience of detection, iron oxide red is used as the pigment in each coating, and the thickness of the sample coating is 80 μm; the performance of each of the above coatings is detected.
[0073] 1. Weather resistance: According to GB / T 1865 "Paints and varnishes - Artificial weathering and exposure to artificial radiation (filtered xenon-arc radiation)", the prepared coating sample plate of 150 mm × 70 mm × 1 mm is placed in a xenon lamp aging test chamber. Set the blackboard temperature to 65 °C, the relative humidity to 50%, the light exposure time to 102 min, and the water spraying time to 18 min as one cycle, and continuously conduct a 1000 h test. After the test, according to GB / T 1766 "Rating method for the aging of paint and varnish coatings", the coating powdering (0 - 5 levels, 0 level no powdering, 5 level severe powdering) situation is rated. The results are shown in Table 1 below.
[0074] 2. Corrosion resistance: Referring to GB / T 1771 "Determination of resistance to neutral salt spray of paints and varnishes", the coating sample plate of 150 mm × 100 mm × 1 mm is placed in a salt spray test chamber, and a 5 wt% sodium chloride solution is used, and the test is carried out under the conditions of a temperature of 35 °C and continuous spraying. Observe the sample plate every 24 h, and record the time when corrosion phenomena (at least one of blistering, rusting, and peeling) occur. The results are shown in Table 1 below.
[0075] 3. Hardness: According to GB / T 6739 "Paints and varnishes - Determination of film hardness by pencil method", different hardness specification pencils are sharpened, ground flat on the plane of 400# water sandpaper, and a 1 cm long line segment is drawn on the coating surface at an angle of 45° with a force of 1 kg at a uniform speed. Each hardness is tested 3 times. The coating hardness is represented by the maximum pencil hardness at which the coating is not scratched. The results are shown in Table 1 below.
[0076] 4. Abrasion resistance: According to GB / T 1768 "Determination of abrasion resistance of paints and varnishes - Rotating rubber wheel method", using a Taber abrasion tester, a 500 g weight is loaded, a CS-17 rubber wheel is selected, and a 100 mm × 100 mm × 1 mm coating sample is rubbed at a speed of 100 r / min. The sample is weighed every 200 rubs until the coating is worn through to expose the substrate, and the number of rubs when worn through is recorded. The results are shown in Table 1 below.
[0077] 5. Adhesion: In accordance with GB / T 9286 "Cross-cut test for paints and varnishes films", use a cross-cut tool to draw 10 × 10 squares with a side length of 1 mm on the surface of a 100 mm × 100 mm × 1 mm coating sample. When cross-cutting, ensure that the tool is perpendicular and the force is uniform, cutting through the coating to the substrate. Then stick 3M600 tape on the cross-cut area, press it flat with fingers to ensure full contact between the tape and the coating, and then quickly pull up the tape at a 90° angle. Rate according to the 0 - 5 level standard (0 level: no peeling, 5 level: peeling area > 65%). The results are shown in Table 1 below.
[0078] 6. Flame retardancy: According to the UL94 vertical burning test standard, prepare a 125 mm × 13 mm × 3 mm coating sample. Vertically fix the sample on the burning test device, apply a Bunsen burner flame (height 20 mm ± 2 mm, temperature 1000 °C ± 50 °C) to the bottom of the sample for 10 s, then remove the flame, record the burning time of the sample, whether there is dripping, and the situation of re-ignition, and determine the flame retardancy grade (V-0, V-1, V-2, HB, etc., V-0 has the best flame retardancy performance) according to the standard. The results are shown in Table 1 below.
[0079] Table 1 Performance test results
[0080]
[0081] As can be seen from the above results, the waterborne coatings of Examples 1 to 3 have excellent weather resistance, corrosion resistance and flame retardancy, and high hardness, good abrasion resistance and strong adhesion.
[0082] Comparative Example 1 uses ordinary aqueous polyurethane emulsion to replace the fluorocarbon-modified polyurethane dispersion. Due to its highly stable carbon-fluorine bond, the fluorocarbon group has excellent resistance to ultraviolet light and can effectively prevent the coating from degrading under light. The ordinary aqueous polyurethane emulsion lacks such a stable structure. Under long-term ultraviolet irradiation, the polymer chain segments are prone to breakage and oxidation, resulting in more serious powdering and fading phenomena. The coating structure formed by the fluorocarbon-modified polyurethane dispersion is denser and can effectively block the penetration of corrosive media. The molecular arrangement of the ordinary aqueous polyurethane emulsion coating is relatively loose, and chloride ions in sodium chloride solution are more likely to pass through the coating to reach the metal substrate, causing corrosion. The fluorocarbon-modified polyurethane dispersion can endow the coating with closer intermolecular interactions and stronger cohesion, thus showing higher hardness and wear resistance. The intermolecular force of the ordinary aqueous polyurethane emulsion is weak, and when subjected to external friction, the molecular chains are more likely to undergo displacement and breakage. The bonding force between the ordinary aqueous polyurethane emulsion and the substrate is relatively weak. In the cross-cut test, the tape is more likely to pull up the coating from the substrate, resulting in a decrease in the adhesion grade. The fluorocarbon-modified polyurethane dispersion has a synergistic effect with other flame retardant components in the system, jointly improving the flame retardant performance of the coating. After replacing with the ordinary aqueous polyurethane emulsion, this synergistic relationship is disrupted.
[0083] Comparative Example 2 does not add C20-22 alcohol phosphate. C20-22 alcohol phosphate participates in the construction of the molecular structure during the synthesis of the fluorocarbon-modified polyurethane dispersion, affecting the regularity and stability of the polymer. Without it, the molecular structure of the coating has defects and is more prone to chemical bond breakage and decomposition under ultraviolet and thermo-oxidative environments, resulting in a decrease in weather resistance. The structural defects reduce the shielding performance of the coating and make it difficult to effectively block corrosive media. The irregular structure affects the intermolecular interactions, reducing the hardness and wear resistance of the coating to a certain extent and also affecting the flame retardancy.
[0084] In Comparative Example 3, the addition of C20-22 alcohol phosphate is excessive. Excessive C20-22 alcohol phosphate disrupts the balance of the reaction system, interfering with the growth and crosslinking of polymer molecular chains and forming an uneven molecular structure. This uneven structure is more prone to aging degradation under ultraviolet and thermo-oxidative actions, resulting in poor weather resistance. The uneven structure reduces the denseness of the coating, making it easier for corrosive media to penetrate. The chaotic molecular structure leads to a weakening of intermolecular forces, reducing hardness and wear resistance. The structural change affects the chemical bonding and physical adsorption between the coating and the substrate, resulting in a decrease in adhesion. Excessive C20-22 alcohol phosphate interferes with the performance of the fluorocarbon-modified polyurethane dispersion and its synergistic effect with the flame retardant, reducing the flame retardant performance.
[0085] Comparative Example 4 uses zirconium phosphate to replace the zirconium phosphate-polyaniline core-shell flame retardant. Polyaniline has certain redox activity and corrosion inhibition effect, and can form a protective film on the metal surface to inhibit the corrosion of the metal and protect the ZnNiAl-LDH two-dimensional layered trimetallic hydroxide from the acidic influence of zirconium phosphate. When only zirconium phosphate is used, the lack of this protective effect of polyaniline results in a decrease in the corrosion resistance of the coating. The core-shell structure formed by polyaniline and zirconium phosphate enhances the mechanical properties of the coating. After replacement, the hardness and wear resistance of the coating decrease. The conjugated structure of polyaniline and the protection of ZnNiAl-LDH two-dimensional layered trimetallic hydroxide from being affected contribute importantly to improving the flame retardant performance of the coating. After only replacing with zirconium phosphate, the flame retardant grade decreases.
[0086] Comparative Example 5 The zirconium phosphate is not surface pretreated. γ-Aminopropyltriethoxysilane is used to surface pretreat the zirconium phosphate to enhance the bonding force between the zirconium phosphate and polyaniline and form a stable core-shell structure. When not treated, the bonding between the two is not firm and peeling will occur during high-speed dispersion and grinding, and the zirconium phosphate will also affect the ZnNiAl-LDH two-dimensional layered trimetallic hydroxide, resulting in a decrease in various indicators, and the performance is close to that of Comparative Example 4.
[0087] Comparative Example 6 does not add the ZnNiAl-LDH two-dimensional layered trimetallic hydroxide. ZnNiAl-LDH has a special layered structure and can play a role in blocking corrosive media and ion exchange buffering. After its absence, the shielding performance of the coating decreases, and the ions in the sodium chloride solution are more likely to reach the metal substrate, accelerating corrosion. The presence of ZnNiAl-LDH helps to enhance the overall mechanical properties of the coating. Without adding, the hardness and wear resistance will decrease slightly. ZnNiAl-LDH can have a synergistic effect with other flame retardant components. When lacking, the flame retardant grade decreases.
[0088] Comparative Example 7 does not add C18-36 acid glycol ester. C18-36 acid glycol ester has the function of improving the film-forming performance of the coating and increasing the density of the coating. When not added, the density of the coating decreases and various properties decline.
[0089] Comparative Example 8 The zirconium phosphate-polyaniline core-shell flame retardant is replaced, and the ZnNiAl-LDH two-dimensional layered trimetallic hydroxide is not added. Lacking polyaniline and ZnNiAl-LDH, the coating loses their protective effects on ultraviolet rays and thermal oxygen and the structure strengthening effect, and is more likely to age under ultraviolet irradiation. Lacking both the corrosion inhibition effect of polyaniline and the blocking effect of ZnNiAl-LDH, the metal substrate is easily corroded. Due to the lack of key strengthening components, the mechanical properties of the coating decrease significantly. The instability of the structure and the lack of components lead to poor adhesion between the coating and the substrate. Losing the synergistic effect of polyaniline and ZnNiAl-LDH with other flame retardant components, the flame retardant performance decreases.
Claims
1. A water-based coating for energy storage equipment, characterized in that: The water-based coating comprises the following raw materials in parts by weight: 10 to 15 parts of fluorocarbon modified polyurethane dispersion, 15 to 20 parts of water-based epoxy ester resin, 30 to 35 parts of water-based silicone modified acrylic resin, 0.5 to 1 part of ZnNiAl-LDH two-dimensional layered trimetallic hydroxide, 6 to 8 parts of zirconium phosphate-polyaniline core-shell flame retardant, 8 to 10 parts of nano-silicon dioxide, 4 to 6 parts of water-based polycarbodiimide, 1 to 2 parts of nano-cerium oxide, 0.5 to 0.8 parts of polyether modified silicone defoamer, 3 to 5 parts of C18-36 acid glycol ester, 0.3 to 0.8 parts of leveling agent, 3 to 6 parts of pigment, 5 to 8 parts of 1-ethoxy-2-propanol, and the balance is water. The solid content is 45wt% to 50wt%.
2. The water-based coating for energy storage equipment according to claim 1, characterized in that: The preparation method of the fluorocarbon modified polyurethane dispersion comprises the following steps: according to the mass proportion, 40 to 50 parts of isophorone diisocyanate, 20 to 25 parts of hexafluorobutanediol, 30 to 35 parts of polyoxypropylene ether diol and 3 to 5 parts of C20-22 alcohol phosphate are stirred and mixed uniformly at 75 to 85° C. under nitrogen protection to obtain a mixed solution A, dibutyltin dilaurate is added, stirred and reacted to obtain a reaction solution B; the temperature is lowered to 55 to 65° C., 5 to 8 parts of dimethylol propionic acid and 100 to 120 parts of acetone are added, stirring and reacting is continued, after the reaction is completed, triethylamine is added to neutralize the pH value to 7 to 8, and then 120 to 150 parts of deionized water are added under high-speed shearing to form a stable dispersion with a particle size of less than 200 nm, and acetone and part of the deionized water are removed by reduced pressure distillation to obtain a fluorocarbon modified polyurethane dispersion with a solid content of 40 wt% to 50 wt%.
3. The water-based coating for energy storage equipment according to claim 2, characterized in that: The added amount of dibutyltin dilaurate is 0.05% to 0.08% of the mass of the mixed solution A.
4. The water-based coating for energy storage equipment according to claim 2, characterized in that: The rotation speed of the stirring reaction is 300 r / min to 500 r / min; the time of the stirring reaction is 3 h to 4 h; the rotation speed of the high-speed shearing is 3000 rpm to 5000 rpm.
5. The water-based coating for energy storage equipment according to claim 1, characterized in that: The preparation method of the zirconium phosphate-polyaniline core-shell flame retardant comprises the following steps: adding zirconium phosphate to ethanol, uniformly dispersing by ultrasonic, adding γ-aminopropyltriethoxysilane in an amount of 6wt% to 8wt% by weight of the zirconium phosphate, stirring for reaction for 2h to 3h, centrifuging, washing the precipitate with anhydrous ethanol, and drying to obtain treated zirconium phosphate; adding the treated zirconium phosphate to a hydrochloric acid solution, uniformly dispersing by ultrasonic, adding aniline at a mass ratio of aniline:treated zirconium phosphate=(2-3):1 at 2°C to 6°C, mixing uniformly, then adding an ammonium persulfate aqueous solution, stirring for polymerization reaction for 6h to 8h, centrifuging, washing the precipitate with deionized water and ethanol alternately, and drying to obtain the zirconium phosphate-polyaniline core-shell flame retardant.
6. The water-based coating for energy storage equipment according to claim 5, characterized in that: The particle size of the zirconium phosphate is nanometer-level; the amount of the ethanol used is 10 to 12 times the mass of the zirconium phosphate; the amount of the hydrochloric acid solution used is 10 to 12 times the mass of the zirconium phosphate after treatment; the hydrochloric acid solution is a 1 mol / L to 1.5 mol / L hydrochloric acid aqueous solution, and the hydrochloric acid solution contains 5 g / 100 mL to 8 g / 100 mL of camphorsulfonic acid; the concentration of the ammonium sulfate aqueous solution is 50 g / 100 mL to 60 g / 100 mL.
7. The water-based coating for energy storage equipment according to claim 5, characterized in that: The frequency of the ultrasonic dispersion is 40kHz-60kHz, the power is 150W-250W, and the time is 30min-60min; the speed of the stirring is 300r / min-500r / min; and the centrifugation is performed at 5000r / min-8000r / min for 10min-20min.
8. The water-based coating for energy storage equipment according to claim 5, characterized in that: The washing with anhydrous ethanol is performed 2 to 3 times; the washing with deionized water and ethanol is performed alternately 2 to 3 times each; and the drying is performed at 60° C. to 80° C. in vacuum for 4 to 8 hours.
9. The method for preparing a water-based coating for energy storage equipment according to claim 1, characterized in that: The steps include: S1: mixing ZnNiAl-LDH two-dimensional layered trimetallic hydroxide, zirconium phosphate-polyaniline core-shell flame retardant, nano-silicon dioxide and nano-cerium oxide uniformly by air flow according to mass fractions to obtain a mixed powder; S2: According to the mass proportions, water-based epoxy ester resin, water-based silicone-modified acrylic resin and 1-ethoxy-2-propanol are stirred and mixed, and then mixed powder and pigment are added, and then polyether-modified silicone defoamer, leveling agent and C18-36 acid glycol ester are added in sequence, and stirred and mixed, and finally water-based polycarbodiimide and fluorocarbon-modified polyurethane dispersion are added, and stirred and mixed to obtain a mixture; S3: The mixture is transferred to a high-speed disperser for high-speed dispersion, and then ground, water is added to adjust the solid content of the system to 45wt% to 50wt%, and stirred to mix evenly to obtain a water-based coating.
10. The method for preparing a water-based coating for energy storage equipment according to claim 9, characterized in that: The stirring and mixing speed is 300r / min to 500r / min, and the stirring and mixing time is 15min to 20min; the high-speed dispersion is 3000rpm to 5000rpm for 30min to 60min; The grinding parameters are as follows: the grinding medium is zirconium oxide with a particle size of 0.1 mm to 0.3 mm, the grinding speed is 1500 rpm to 2500 rpm, and the feed rate is 2 L / min to 3 L / min.
Citation Information
Patent Citations
Aqueous fire-proof corrosion-proof paint for steel structure and preparation method thereof
CN104130638A
Aqueous fluorine-containing resin and preparation method thereof
CN109912770A
Flame retardant, fireproof coating and preparation method
CN116082875A
Scrubbing-resistant inorganic coating emulsion composition and preparation method thereof
CN119684859A
Phenylboronic acid grafted modified zirconium phosphate-based flame retardant and preparation method therefor
WO2022160673A1